THE INFLUENCE OF HEATING TREATMENT ON PHYSICALPROPERTIES OF POROUS SILICON - Alwan, Alwan M; Abd alzahra, Narges Z (Al-Nahrain Journal of Science, 2018)
In this work we studying the effect of thermal treatment on the electrical and conduction properties of metal /porous silica /n-si /metal prepared by photo electro chemical etching for etching time (15 min. Oxidation occur in oxidation time (15-150)sec at 750Ċ.After investigated current–voltage (J-V)measurement we found increase in rectification ratio ,barrier height increase with oxidation time, the rectification ration was 5 before oxidation will be 21 after 30 s oxidation time, barrier height value was (0.756eV) will be( 0.85eV) at oxidation time 30 s ,the ideality factor after oxidation was 15 will be 2.75 at 30 sec of oxidation time mean that the device approach from the ideality characteristics.